Combination of bis (α‐furancarboxylato) oxovanadium (IV) and metformin improves hepatic steatosis through down‐regulating inflammatory pathways in high‐fat diet‐induced obese C57BL/6J mice. Issue 6 (14th March 2021) - Liu, Quan; Li, Linyi; Gao, Lihui; Li, Caina; Huan, Yi; Lei, Lei; Cao, Hui; Li, Ling; Gao, Anli; Liu, Shuainan; Shen, Zhufang
Abstract: The effects of the combination of bis (α‐furancarboxylato) oxovanadium (IV) (BFOV) and metformin (Met) on hepatic steatosis were investigated in high‐fat diet‐induced obese C57BL/6J mice (HFC57 mice) for 6 weeks. Oral glucose tolerance test was performed to evaluate glucose metabolism. Moreover, blood and hepatic biochemical and histological indices were detected. Besides, Affymetrix‐GeneChip analysis and Western blot of the liver were performed. Comparing to the monotherapy group, BFOV + Met showed more effective improvement in glucose metabolism, which decreased the fasting blood glucose, insulin levels and improved insulin sensitivity in HFC57 mice. BFOV + Met significantly decreased serum ALT and AST activities and reduced hepatic triglyceride content and iNOS activities, accompanied by ameliorating intrahepatic fat accumulation and hepatocellular vacuolation. Enhanced hepatic insulin signalling transduction and attenuated inflammation pathway were identified as the major pathways in the BFOV + Met group. BFOV + Met significantly down‐regulated the protein expression levels of MMPs, NF‐κB, iNOS and up‐regulated phosphorylation of AKT and AMPK levels. We concluded that a combination of BFOV and metformin ameliorates hepatic steatosis in HFC57 mice via alleviating hepatic inflammation and enhancing insulin signalling pathway, suggesting that the combination of BFOV and metformin is a potential treatment for hepatic steatosis.